Historical account - Keenan, J. J. (1901)
"The Official unpublished record of the visit of the Duke and Duchess of Cornwall and York to the Commonwealth of Australia for the opening of Federal Parliament".
Manuscript reference no. : NLA MS 7072.
Photocopy available.
Keywords: George -- V, -- King of Great Britain, -- 1865-1936.; Mary, -- Queen, consort of George V, King of Great Britain, -- 1867-1953.; Visits of state -- Australian Capital Territory -- Canberra; Royal visitors -- Australian Capital Territory -- Canberra; Federal government -- Australia -- History; Australia -- History -- 20th century